Assessing the Nexus between Climate Change and Public Health in Nepal: A Comprehensive Exploration of Impacts, Vulnerabilities, and Adaptive Strategies - Sigdel, Uddhav; Rimal, Sudhir Kumar; Subedi, Ramita; Bhattarai, Shiva Prasad; Dhungel, Harka Bahadur; Pokharel, Shailaja; Adhikari, Laxmi (Nepal Journal of Multidisciplinary Research, 2023)
Climate change and variability exert a global influence, affecting individuals and regions across the world. However, its impact is particularly pronounced in specific geographical areas and their inhabitants. Nepal, a globally recognized mountainous country, encompasses 18 percent of the world's mountainous terrain and spans 4.3 million km2 across eight Asian countries: Nepal, Bhutan, Afghanistan, Bangladesh, China, India, Myanmar, and Pakistan. These Asian regions are experiencing a warming trend that surpasses the global average, accompanied by a significant increase in precipitation over the past six decades, leading to heightened frequency and intensity of specific extreme events. The alterations in temperature and precipitation have already impacted and are expected to continue affecting various climate-dependent sectors such as hydrology, agriculture, biodiversity, and human health. This paper aims to document the historical and anticipated impacts of climate change on the health and well-being of Nepal's population, providing adaptation and mitigation strategies to alleviate these effects. Additionally, the study assesses the indirect impact of agriculture and other human-related issues on human health and well-being. Utilizing narrative review processes, the research concludes the outlined issues. In Nepal, climate change contributes to complex challenges, resulting in the proliferation of infectious diseases, non-communicable diseases (NCDs), malnutrition, and injuries, as evident from this review. Consequently, the prompt implementation of climate change adaptation and mitigation measures is imperative to protect the vulnerable populations residing in the country.